Genome-wide Identification of Metal Tolerance Protein Genes in Peanut: Differential Expression in the Root of Two Contrasting Cultivars Under Metal Stresses - Wang, Xueqin; Wang, Chaohui; Zhang, Zheng; Shi, Gangrong (Frontiers in Plant Science, 2022)
Metal tolerance proteins (MTP) are Me2+/H+(K+) antiporters that play important roles in the transport of divalent cations in plants. However, their functions in peanut are unknown. In the present study, a total of 24 AhMTP genes were identified in peanut, which were divided into seven groups belonging to three substrate-specific clusters (Zn-CDFs, Zn/Fe-CDFs, and Mn-CDFs). All AhMTP genes underwent whole genome or segmental gene duplication events except AhMTP12. Most AhMTP members within the same subfamily or group generally have similar gene and protein structural characteristics. However, some genes, such as AhMTP1.3, AhMTP2.4, and AhMTP12, showed wide divergences. Most of AhMTP genes preferentially expressed in reproductive tissues, suggesting that these genes might play roles in metal transport during the pod and seed development stages. Excess metal exposure induced expressions for most of AhMTP genes in peanut roots depending on cultivars. By contrast, AhMTP genes in the root of Fenghua 1 were more sensitive to excess Fe, Cd and Zn exposure than that of Silihong. Stepwise linear regression analysis showed that the percentage of Fe in shoots significantly and positively correlated with the expression of AhMTP4.1, AhMTP9.1 and AhMTPC4.1, but negatively correlated with that of AhMTPC2.1 and AhMTP12. The expression of AhMTP1.1 showed a significant and negative correlation with the percentage of Mn in shoots. The percentage of Zn in shoots was significantly and positively correlated with the expression of AhMTP2.1, but was negatively correlated with that of AhMTPC2.1. The differential responses of AhMTP genes to metal exposure might be, at least partially, responsible for the different metal translocation from roots to shoots between Fenghua 1 and Silihong.